2020
DOI: 10.1590/1980-5918.33.ao05
|View full text |Cite
|
Sign up to set email alerts
|

Use of lung expansion techniques on drained and non-drained pleural effusion: survey with 232 physiotherapists

Abstract: Introduction: Techniques for lung expansion seem to benefit patients with drained and undrained pleural effusion, but there is a lack of evidence to indicate which technique is best in each situation. Currently, the therapeutic choices of respiratory physiotherapists serving this population are not known. Objective: To know which lung expansion techniques are chosen by chest physiotherapists who assist patients with drained and non-drained pleural effusion. Method: Through the announcement of the Federal Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Deep breathing, incentive spirometry, and positive pressure exercises were all effective lung expansion techniques employed in patients who had drained pleural effusions [11]. Chest mobility exercises improve chest wall, trunk, and shoulder mobility, even focusing on depth of inspiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep breathing, incentive spirometry, and positive pressure exercises were all effective lung expansion techniques employed in patients who had drained pleural effusions [11]. Chest mobility exercises improve chest wall, trunk, and shoulder mobility, even focusing on depth of inspiration.…”
Section: Discussionmentioning
confidence: 99%
“…The primary interventions for rehabilitating patients with deteriorating health status due to respiratory problems include patient education, airway clearance procedures, breathing strategies, and a graded exercise training program [ 10 ]. Deep breathing, incentive spirometry, and positive pressure exercises were all effective lung expansion techniques employed in patients who had drained pleural effusions [ 11 ]. Chest mobility exercises improve chest wall, trunk, and shoulder mobility, even focusing on depth of inspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Deep breathing exercises and lung expansion techniques have been widely used to prevent complications in different chronic respiratory diseases and after surgical procedures [55][56][57][58]. However, their efficacy remains uncertain.…”
Section: Techniques For Lung Expansionmentioning
confidence: 99%
“…Deep breathing exercises are based on producing an active inspiration with a breath hold, permitting a maximum and slow breath, before a passive expiration. This technique can be applied in patients with drained and undrained pleural effusions; a survey has found that it is the most commonly used technique in these patients [56]. Deep breathing exercises have been evaluated in patients after upper abdominal surgery in a randomised control trial; results show that neither thoracoabdominal mechanics nor pulmonary complications were modified using this technique [58].…”
Section: Techniques For Lung Expansionmentioning
confidence: 99%
“…Several publications have suggested that IS is ineffective [8,10]. Nevertheless, nearly 42% of physiotherapists keep using IS after thoracic surgical procedures [11]. In contrast, some studies have shown that when IS is adequately used, it may lead to beneficial outcomes [12,13].…”
Section: Introductionmentioning
confidence: 99%